العلامة العامري "ت. 893 هـ." ومنهجه في الاقتباس من كتب الصحاح في كتابه بهجة المحافل وبغية الأماثل في تخليص السير والمعجزات والشمائل - السعدون، على زامل هلال; جاسم، خالد محمد (الجامعة المستنصرية - كلية التربية الأساسية, 2022)
دأب العلماء في القديم والحاضر على دراسة السيرة والشمائل النبوية واعتمدوا في مؤلفاتهم على كثير من الموارد التي أخذوا منها هذه السيرة المباركة لا سيما أهل الحديث النبوي الذي نقلوا الأحاديث الشريفة الصحيحة عن الرواة، ومن هؤلاء المؤلفين العلامة المحدث يحيى بن أبي بكر بن محمد بن يحيى بن محمد العامري المكنى أبو زكريا، المتوفى سنة (ت: 893ه)، في كتابه (بهجة المحافل وبغية الأماثل في تلخيص السير والمعجزات والشمائل) ومن منهجه في كتابه أنه اقتبس المعلومات من مصادر عدة وموارد كثيرة ومن هذه الموارد الأحاديث الشريفة من كتب الصحاح، ولأهمية هذا الكتاب أردت بيان موارده من كتب الصحاح. Scholars, in the old and present have been studying the biography and merits of the Prophet, and they relied in their books on many resources from which they took this blessed biography, especially the people of hadith who transmitted authentic hadiths from the narrators. Of those narrators was the scholar “Muhammad al-Amiri, nicknamed Abu Zakaria” who died in the year (died : 893 AH), in his book (Bahjat al-Mahafil Wa Bighyat al-Amthal in summarizing biographies, miracles and merits) and his method in his book is that he quoted information from many sources and many resources, and among these resources are the honorable hadiths from the books of Al-Sihah. For The importance of this book I wanted to show its resources from Al-Sihah books.
Keywords: العامري، يحيى بن أبى بكر بن محمد بن يحيى، ت. 893 هـ. -- السيرة النبوية -- الحديث النبوي